The Comprehensive Evolution of Ornamentation in Medieval and Post-Seljuk Architecture - Nazer, Zeynab; Rabb, Peter (İstanbul Üniversitesi, 2025)
This research examines the evolution of ornamentation in Medieval and post-Seljuk architecture, focusing on key elements such as geometric patterns, floral motifs, calligraphy, stucco, tilework, and muqarnas. This study analyzes architectural features from different centuries and regions, highlighting how these decorative elements reflect the cultural and religious values of the Seljuk Empire. A comparative approach is used to explore the stylistic variations and advancements in architectural ornamentation in areas such as Anatolia, Persia, and Central Asia. The findings reveal a steady development in complexity and artistic expression across time. Geometric patterns were the dominant ornamentation form, reflecting Islamic unity and infinity principles. As time passed, floral motifs became more prominent, and calligraphy evolved into a central decorative feature in religious contexts. The use of stucco and tilework also grew more sophisticated, with tile decoration reaching its artistic peak in the 13th and 14th centuries. Although initially minimal, Muqarnas gained significant importance in later centuries, particularly in religious structures. This study underscores the lasting impact of Seljuk ornamentation on Islamic architectural heritage. The evolution of these elements not only defined the aesthetic values of the Seljuk period but also influenced architectural styles in the broader Islamic world and beyond, shaping the artistic landscape of regions under Seljuk influence.
Keywords: Architecture (Other); Mimarlık (Diğer)